Treatment of chronic total occlusions in native coronary arteries by drug-coated balloons without stenting - A feasibility and safety study. (15th December 2016) - Köln, Philine J.; Scheller, Bruno; Liew, Houng Bang; Rissanen, Tuomas T.; Ahmad, Wan Azman Wan; Weser, Ralf; Hauschild, Telse; Nuruddin, Amin Ariff; Clever, Yvonne P.; Ho, Hee Hwa; Kleber, Franz X.
Abstract: Background: Chronic total occlusions remain one of the biggest challenges for interventional cardiologists and the high risk of restenosis and stent thrombosis is still a major problem. Drug-coated balloons showed favorable results for the treatment of in-stent restenosis and other lesion types. The aim of this study was to evaluate the feasibility and outcome of a drug-coated balloon only approach for chronic total occlusion. Methods: We included 34 patients with a native chronic total occlusion treated only by drug-coated balloons. A visual residual stenosis of 30% or less without major dissection was considered a satisfactory percutaneous intervention result according to the German Consensus Group recommendations for drug-coated balloon use. We collected clinical and procedural data. Angiograms were conducted during the procedure and at follow-up. Quantitative coronary analysis was performed and mean and minimal lumen diameter and late luminal changes were assessed. Results: The recanalization was considered satisfactory in 79.4% (n = 27). Restenosis occurred in 11.8% (n = 4) and reocclusion in 5.9% (n = 2). Out of the 27 patients with a satisfactory initial result, 3.7% (n = 1) had reocclusion and 3.7% (n = 1) had restenosis. In the subgroup without satisfactory result (n = 7), restenosis occurred in 3 patients (42.9%) and reocclusion in 1 patient (14.3%). A luminal increase was found in 67.6% (n = 23) and mean late luminal gain was 0.11 ± 0.49 mm. Angina class improved significantly (p < 0.001). There was no death or myocardial infarction. Conclusions: Drug-coated balloon angioplasty without stenting is a feasible and well-tolerated treatment method for chronic total occlusions if the predilatation result is good.